Impact of performance management system on employees productivity in the public sector in Ghana. A case study Asokore Mampong Municipal Assembly in the Ashanti Region. - Kenneth Kitinkawa (KNUST, 2025)
A Thesis In Partial Fulfillment Of The Requirements For The Award Of Master Of Public Administration.